Simplification of strong ground motion considering inelastic responses of structures. - Sakai, Yuki
Simplification of strong ground motions to 1 cycle sine waves was investigated from the elastic and inelastic earthquake response analyses and response analyses under sine wave input using single degree of freedom systems. Strong ground motions could be simplified to 1 cycle sine waves if large plastic deformations, with ductility factor more than 2, were asuumed. This is because the approximate maximum responses from input sine waves are determined by the initial response cycle, due to period elongation and plastic energy dissipation of the systems. A sine wave whose acceleration amplitude is the peak ground acceleration (PGA) and whose period is that of an equivalent 1 cycle sine wave is proposed. The period of an equivalent sine wave is easily obtained from the elastic response acceleration spectrum of a seismic record. This means that the inelastic responses are approximately determined by the PGA and an equivalent 1 cycle sine wave period. Therefore, an equivalent 1 cycle sine wave period provides a single index to express the frequency characteristics of a strong ground motion.
Keywords: Simplification; Earthquake strong motion prediction; Required strength spectrum; Single degree of freedom system; 1 cycle sine wave; Ductility factor